BURNOUT RISK OF FOSTER GUARDIAN; AN ANALYSIS OF AVOIDANCE STRATEGIES - Badruddin, M Fuad; Baharun, Hasan; Solehah, Imbrotus (Nurul Jadid University, 2023)
This study presents the handling of burnout in foster care in terms of service to students. Foster guardians play a significant role as second parents who must control, foster, motivate, and protect students. This foster guardian has fostered children of more than ten people, where the foster guardian must recognize the students' character one by one, which causes burnout in serving the students. This study aims to understand strategies to avoid burnout in foster care by serving students with unique characteristics. This study used a qualitative method with a case study type. This study focused on one case: the caregiver who experienced burnout in serving students. The results showed that burnout in foster care could be handled in several ways: ruhul jihad, guardianship mentoring, Knowledge sharing and caregiver advice. The research implies that foster carers must have innovation and creativity in dealing with foster children so that foster carers experience satisfaction in serving students.